Penilaian Kesehatan Keuangan Koperasi Berdasarkan Peraturan Deputi Bidang Pengawasan Kementerian Koperasi dan UKM RI Nomor: 07/PER/DEP.6/IV/2016 pada KSPPS Tanah Sirah Piai Nan XX Kota Padang Periode 2016-2018 - Dwila Maresti; Sriwahyuni Riza (Ekonomis: Journal of Economics and Business, 2020)
The purpose of this study was to determine the level of health of a Savings and Loan Cooperative and Sharia Financing (KSPPS) in one of the Padang City sub-districts namely Tanah Sirah Piai Nan XX in 3 (three) years of operation. The research is intended to help the Padang City Cooperative Office to find out the health condition of cooperatives in the Padang City area as well as the KSPPS Cooperative to find out the health of cooperatives managed. Based on quantitative research with a descriptive approach, this health assessment analysis refers to the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 07 / Per / Dep.6 / IV / 2016 concerning Guidelines on Health Assessment for Savings and Loans Cooperatives and Sharia Financing and Units Savings and Credit Sharia Financing. The results showed the health level of KSPPS Tanah Sirah Piai XX was concluded that KSPPS Tanah Sirah Piai Nan XX was quite healthy.